Acromegaly and lung cancer: a rare association - Silva Júnior, Geraldo B. (2008)
The authors present a clinical case report of a 71 year-old man with history of productive cough, left hemiparesis, focal upper limb convulsions and weight loss, of five months duration. The patient had lost 7kg in the same time period. The only abnormality noted on physical examination were acromegalic facies and basal rhonchus on chest auscultation. Chest x-ray showed a hypotransparent image in the right lung and important cardiomegaly. Laboratory tests showed Hb=13g/dL, Hct=41%, WBC=11200/mm3, Platelets=264000/mm3, Ur=123 mg/dL, Cr=2.5 mg/dL, Na=133 mEq/L, K=6.1 mEq/L, Ca=11 mg/dL, fast glucose=89 mg/dL, uric acid=11 mg/dL, Albumin=4.4 g/dL, AST=44 UI/mL, ALT=20 UI/mL, LDH=561 UI/mL. Antibiotics for respiratory infection were started and GH and IGF-I blood analysis for suspected acromegaly were performed. After improvement of renal function with fluid administration (Ur=47 mg/dL e Cr= 1.2 mg/dL), CT of the cranium, thorax and abdomen were performed. Cranium CT showed lesions suggestive of secondary neoplastic metastases. Thoracic CT revealed a tumoural lesion in the right bronchus. Abdominal CT showed an aortic aneurysm. The patient started radiotherapy for cerebral metastases, with improvement of neurologic manifestations. Biopsy of the pulmonary lesion revealed a non-small cell lung carcinoma and the patient started chemotherapy. The dosage of IGF-I was 482 (adjusted reference for gender and age = 64-188) and GH was 0.57 (reference= 0.06-7), compatible with acromegaly. The patient was discharged for home care follow-up and died one week later